Statistical Recognition of OAM States in Free-Space Optical System - Qinnan Zhu; Guowei Yang; Zhiyu Yuan; Meihua Bi; Xuefang Zhou; Miao Hu (IEEE Photonics Journal)
The orbital angular momentum (OAM) states are used for OAM modulation and OAM multiplexing in free-space optical (FSO) communication systems to enhance the transmission quality and capacity. Although a few impactful methods had been developed to measure static OAM states, the fast and accurate recognition of dynamic OAM states in FSO communications remains a challenge due to the OAM crosstalk easily induced by the atmospheric turbulence. In this paper, we present a new simple statistical recognition method realized by utilizing the turbulence-induced crosstalk distribution, other than the routine way to use the spatial intensity patterns. The proposed method is based on acquiring the priori OAM crosstalk distribution of the training optical data, and then using similarity analysis to recognize the OAM states of the information optical data. Its availability and accuracy are validated through the computer simulations. The recognition accuracy under relatively strong turbulence conditions can be improved by using wavefront compensation and specific distance calculation.